Effectiveness of Broad-Spectrum Probiotics in Reducing Symptoms and Improving Quality of Life in Adults with Irritable Bowel Syndrome (IBS): A Meta-Analysis of Randomized Controlled Trials - Wandala, Abali; Monis , Manahil; Hussain, Azzah Khadim; Hashim, Maria; Haider, Rafia; Malallah, Mohammed Ali Yassin; Khalid, Roheen; Abukhater , Noor Ayman Khalil Salim Nawas (Indus Journal of Bioscience Research, 2025)
Background: Irritable Bowel Syndrome (IBS) is a chronic functional gastrointestinal disorder characterized by recurrent abdominal pain and altered bowel habits, significantly impairing patients’ quality of life. Emerging evidence suggests that gut dysbiosis plays a central role in IBS pathophysiology, with probiotics offering a potential therapeutic approach. However, inconsistent findings across studies highlight the need for a comprehensive meta-analysis to assess the effectiveness of broad-spectrum probiotics in IBS management. Objective: This meta-analysis aimed to evaluate the efficacy of broad-spectrum probiotics in reducing IBS symptoms and improving quality of life in adults. Methods: Following PRISMA guidelines, a systematic search was conducted across PubMed, Embase, Cochrane Library, and Web of Science to identify randomized controlled trials (RCTs) investigating broad-spectrum probiotics in IBS management. Studies assessing symptom severity, quality of life, and hospitalization rates with a minimum intervention duration of eight weeks were included. Data were extracted on study characteristics, intervention details, and clinical outcomes. Statistical analysis was performed using random-effects models to compute pooled effect sizes, odds ratios, and heterogeneity indices. Results: Eight RCTs comprising 2,575 participants met the inclusion criteria. Broad-spectrum probiotics significantly reduced IBS symptom severity compared to placebo (effect size range: -1.2 to -0.8, p < 0.01) and improved patient-reported quality of life (IBS-QOL score improvements). Subgroup analysis indicated that diarrhea-predominant IBS (IBS-D) patients, multi-strain probiotics, and longer treatment durations were associated with greater symptom relief. Heterogeneity ranged from 30% to 60%, and publication bias was identified but did not significantly alter the results after adjustment. Conclusion: This meta-analysis supports broad-spectrum probiotics as an effective IBS therapy, highlighting multi-strain, high-dose, long-duration benefits. Further large-scale RCTs needed.